A Prospective Study of Thyroid Dysfunction in Type-2 Diabetes Patients in a Rural Population - B Satish Babu (International Journal of Medical Arts, 2022)
Background: The thyroid gland is primarily in charge of regulating energy balance and metabolism. Thyroid hormone [TH] is thought to be an important anticipating factor for developing type 2 diabetes mellitus [T2DM] since insulin secretion and glucose metabolism are most strongly associated with the pathophysiology of T2DM. However, few studies in the general population with euthyroid status have looked at the association between TH, thyroid-stimulating hormone [TSH] and T2DM. The Aim of The Work:  The study aimed to assess thyroid function in type 2 diabetes mellitus and to know the spectrum of thyroid diseases in rural populations.Patients and Methods: A cross-sectional study was carried out at St Peters Medical College Hospital and Research Centre, Hosur. The study selected type 2 diabetics attending outpatient department [OPD]/wards in the Department of General Medicine. Thyroid profile tests were performed on all participants in the trial to determine their thyroid status, as well as a target organ evaluation for diabetes, were also observed. FNAC, Thyroid Peroxidase Antibody [TPO-Ab], and thyroid ultrasound sonography test [USG] were done as required.Results: Thyroid disorders were found in 40%, sub-clinical hypothyroidism in 25%, hypothyroidism in 10%, and hyperthyroidism in 5% of the cases. In the current study, 58 female patients and 42 male patients were present. Males [16.66%] had a lower incidence of thyroid disorders than females [56.89%]. Glycemic control was suboptimal in hyperthyroidism patients [55.5%]. The occurrence of thyroid diseases was unrelated to the duration of diabetes. Sub-clinical hypothyroidism was mostly observed in patients with severe diabetic microvascular complications.Conclusion: The prevalence of thyroid disorders in T2DM was 40%. Females were more likely to have subclinical hypothyroidism. Glycemic control was poor in diabetics with hyperthyroidism. Patients with subclinical hypothyroidism had severe diabetic complications. Thyroid dysfunction was unaffected by the duration of diabetes.